2012
DOI: 10.1103/physrevc.85.011302
|View full text |Cite
|
Sign up to set email alerts
|

Low-lying neutronfp-shell intruder states in27Ne

Abstract: The quenching of the N =20 shell gap in neutron-rich nuclei is investigated by studying the singleparticle structure of 27 Ne via neutron transfer using a 26 Ne beam. Two low-lying negative parity intruder states have been observed, the lowest of which is identified as J π = 3/2 − , confirming earlier speculations. A level identified as 7/2 − is observed higher in energy than the 3/2 − , contrary to the ordering at β-stability and at an energy significantly different to the predictions of previous shellmodel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 35 publications
6
34
0
Order By: Relevance
“…Recent experimental observations [21][22][23][24] have brought remarkable credit to the theoretical description of Fig.1 around (N=16, Z=8) suggesting an inversion between the 1p 3/2 and 0f 7/2 orbits in the N=15 and N=17 Ne isotopes. These experiments have also demonstrated that the N=20 gap is small.…”
Section: Introductionmentioning
confidence: 85%
“…Recent experimental observations [21][22][23][24] have brought remarkable credit to the theoretical description of Fig.1 around (N=16, Z=8) suggesting an inversion between the 1p 3/2 and 0f 7/2 orbits in the N=15 and N=17 Ne isotopes. These experiments have also demonstrated that the N=20 gap is small.…”
Section: Introductionmentioning
confidence: 85%
“…4 were observed in a recent in-beam γ -ray spectroscopic study [22], although spin-parity assignments were not made. In the case of the excited states of 27 Ne, the SDPF-M interaction has some difficulty predicting the energy of the 7/2 − level, found near 2 MeV in a recent 26 Ne(d, p) reaction study [21]. 27 Ne is based on Refs.…”
Section: A Shell-model Calculationsmentioning
confidence: 99%
“…Recent 26 Ne(d, p) reaction studies have demonstrated that the lowest 3/2 − state is at 765 keV, while the 27 Ne ground state is 3/2 + [18][19][20][21] (see also Fig. 4 in Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(The spectroscopic factor with rather large experimental errors obtained from a d( 26 Ne, 27 Ne)p reaction can be found, for example, in Ref. [6].) In contrast, I take the model that both the first (3/2 − ) and second (1/2 + ) excited states as the deformed 26 Ne core plus one neutron in the quadrupole-deformed potential.…”
Section: Model and Numerical Calculationsmentioning
confidence: 99%